Was ist mit dem versprochenen Land passiert? Post-Apartheid Südafrika aus der Perspektive Frantz Fanons - Gibson, Nigel C. (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
This paper reviews post-apartheid South Africa through Fanon’s critical analysis of decolonization. Since, for Fanon, apartheid represented the purest form of the Manichean politics of space that characterizes colonialism, a Fanonian perspective on South Africa asks to what extent has the geographical layout of apartheid been remapped? Addressing this question necessitates shifting the “geography of reason” from technical discourses of policy-makers to the lived reality of the “damned of the earth”. From this perspective, Fanon’s critique becomes relevant in two ways, first as a prism to understand the rise of xenophobic violence as a symptom of the degeneration of the idea of South Africa’s “promised land” and second as a way to listen to a new grassroots shack dweller movement, Abahlali baseMjondolo, that is challenging both neoliberal and progressive assumptions by advocating a quite different geographic layout for a “truly democratic” society.